Нistorical aspects of legal opinions of the property - Шкварок, Лідія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
This article analyzes the scientific literature, articles and views of individual philosophers, scientists on the problem of the existence of property in private law of property rights at different stages. The author concludes that the property was shaped by a strong and independent person and involved in building civil society.